Microaccounting and Macroaccounting. - Yu, S. C. (The Accounting Review, 1966)
Abstract The two levels of accounting, microaccounting on one hand and macroaccounting on the other, indicate not only that accounting is a rapidly expanding field but also that accounting plays an important role in today's complex economy. The purpose of this article is to explore the interrelationship between microaccounting and macroaccounting. More specifically, it attempts, firstly, to identify macroaccounting as a branch of accounting; secondly, to examine briefly the interrelationships among the four sub-areas of accounting and economics, i.e., microaccounting, macroaccounting, microeconomics, and macroeconomics; thirdly, to compare some of the basic similarities and dissimilarities between microaccounting and macroaccounting; and finally to explore potential influences of macroaccounting on microaccounting. The article concludes that the demand for additional information from accounting for managerial, investment, and analytical purposes points to the need for more constructive and creative thinking in accounting.